Transformative Business Models as an Accelerator for Digital Transformation of Women's Microenterprises - Abdul Ghonisyah, Ghaling Achmad; Arif, Arif (Universitas Islam Kadiri, 2024)
The issue of digital transformation is currently still a strategic program of the Indonesian government, especially for women micro-enterprises in the regions, as stated in the master plan for the development of the Indonesian digital industry 2023-2045 initiated by BAPPENAS RI. To strive for the achievement of a complete digital transformation, business entities, in this case, women's micro-enterprises must be willing to adopt new business models that are relevant to the needs of a more specific market and experience many behavioral changes in meeting their needs. In this context, the purpose of the research is to investigate how transformative business models can accelerate the digital transformation of women's micro-enterprises in Indonesia, especially in Tasikmalaya. We used a qualitative approach by conducting in-depth interviews with 9 women micro-enterprises using a descriptive coding approach. The contribution of the results of this study explains that transformative business models can accelerate the digital transformation of women's micro-business entities as reflected in how to determine Value Proposition, Functional Architecture, Value Architecture that are relevant to the conditions of digital industry development in Indonesia. However, the results of this study reflect that product innovation is the lowest part carried out by women micro business actors